The Future of Climate-Resilient and Climate-Neutral City in the Temperate Climate Zone - Antoszewski, Patryk; Krzyżaniak, Michał; Świerk, Dariusz (International journal of environmental research and public health, 2022)
The urban heat island (UHI) effect is the main problem regarding a city’s climate. It is the main adverse effect of urbanization and negatively affects human thermal comfort levels as defined by physiological equivalent temperature (PET) in the urban environment. Blue and green infrastructure (BGI) solutions may mitigate the UHI effect. First, however, it is necessary to understand the problem from the degrading side. The subject of this review is to identify the most essential geometrical, morphological, and topographical parameters of the urbanized environment (UE) and to understand the synergistic relationships between city and nature. A four-stage normative procedure was used, appropriate for systematic reviews of the UHI. First, one climate zone (temperate climate zone C) was limited to unify the design guidelines. As a result of delimitation, 313 scientific articles were obtained (546 rejected). Second, the canonical correlation analysis (CCA) was performed for the obtained data. Finally, our research showed the parameters of the UE facilities, which are necessary to mitigate the UHI effect. Those are building density and urban surface albedo for neighborhood cluster (NH), and distance from the city center, aspect ratio, ground surface albedo, and street orientation for street canyon (SC), as well as building height, material albedo, and building orientation for the building structure (BU). The developed guidelines can form the basis for microclimate design in a temperate climate. The data obtained from the statistical analysis will be used to create the blue-green infrastructure (BGI) dynamic modeling algorithm, which is the main focus of the future series of articles.